Efficient expression and purification of rat CRP in Pichia pastoris - Cheng, Bin; Tang, Yu-Long; Gou, Ya-Fei; Li, Jing-Yi; Xu, Tian-Hao; Zhu, Li (Frontiers in Immunology, 2024)
C-reactive protein (CRP) plays a crucial role in the diagnosis and monitoring of the non-specific acute phase response in humans. In contrast, rat CRP (rCRP) is an atypical acute-phase protein that possesses unique features, such as a possible incapacity to trigger the complement system and markedly elevated baseline plasma concentrations. To facilitate in vitro studies on these unique characteristics, obtaining high-quality pure rCRP is essential. Here we explored various strategies for rCRP purification, including direct isolation from rat plasma and recombinant expression in both prokaryotic and eukaryotic systems. Our study optimized the recombinant expression system to enhance the secretion and purification efficiency of rCRP. Compared to traditional purification methods, we present a streamlined and effective approach for the expression and purification of rCRP in the Pichia pastoris system. This refined methodology offers significant improvements in the efficiency and effectiveness of rCRP purification, thereby facilitating further structural and functional studies on rCRP.